Comparison of the Effectiveness of Cognitive Behavioral Training and Acceptance and Commitment Training on High-Risk Behaviors in Self-Injurious Adolescents - Graily Moshkabadi, Elahe; Heydari, Shaban; Fakhri, Mohammadkazem (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Many adolescents face challenges with family, community, and relatives, which may push them towards high-risk behaviors during decision-making stages due to the pressure of these problems. This study compared the effectiveness of cognitive behavioral training (CBT) and acceptance and commitment training (ACT) on high-risk behaviors in self-injurious high school students. Methods and Materials: This quasi-experimental research used a pre-test, post-test, and follow-up design with a control group. The statistical population included self-injurious male adolescents (high school students in District 1 schools) in Sari during the 2021-2022 academic year. From this population, 45 students were selected using purposive sampling and randomly assigned to two experimental groups and one control group (15 students per group). The first experimental group underwent 8 weekly 90-minute sessions based on the CBT training package (Beck, 1976), and the second experimental group underwent 8 weekly 90-minute sessions based on the ACT training package (Hayes et al., 2013). Data collection tools included the High-Risk Behaviors Questionnaire (Zadeh-Mohammadi & Ahmadabadi, 2008) and the Self-Injury Questionnaire (Klonsky & Glenn, 2011). Data were analyzed using SPSS-21 software and statistical tests, including repeated measures ANOVA and two-way ANOVA. Findings: The results showed that both CBT and ACT had significant effects on high-risk behaviors in self-injurious students (F=42.00, P<0.001), with the effectiveness of CBT and ACT being similar on the studied variables. Conclusion: It can be concluded that both CBT and ACT significantly impacted high-risk behaviors in self-injurious students and can be used to address issues in adolescents with self-injury problems.